Spatial Information in the Emergence of Life - Cruz-Rosas, Hugo I.; Miramontes, Pedro (Frontiers in Genetics, 2021)
Information in living systems is part of a complex relationship between internal organization and functionality of life. In a cell, both the genetic-coding sequences and the molecular-shape recognition are sources of biological information. For folded polymers, its spatial arrangement contains the general references about conditions that shaped them, as imprints, defining the data for spatial (conformational) information. Considering the origin of life problem, prebiotic dynamics of matching and transfer of molecular shapes may emerge as a flow of information in prebiotic assemblages. The spatial information is a possible resource for an active system response towards milieu disturbances. Propagation of resilient conformations could be the substrate for structural maintenance through a dynamical molecular scaffolding. The above is a basis for adaptive behavior in potentially biogenic systems. In the present contribution, we explore the role of spatial information in the origin of life and evaluate its implications for the early evolution as a previous step for the arising of sequential information carried out by genetic polymers.